Correlation of potentials and challenges of digital advertising with consumer behaviour in Delta State, Nigeria - Hannah Emuobasa; Harvey G.O. Igben, Ivwrighen (British Journal of Marketing Studies, 2023)
This study is examined the correlation of the potentials and challenges of digital advertising with consumer purchasing behaviour in Delta State, Nigeria. The scope of the study illuminated the potential and challenges of digital advertising while highlighting trends and factors of consumers’ purchasing behaviour. Following a descriptive research design, the questionnaire was used to collect data from 400 respondents drawn from the three senatorial zones in Delta State. Stata software 15.0 was used to test hypothesis and deductions were made from findings that the potential of digital advertising is helping businesses to be more visible not minding the challenges it is facing. Also drawn is the conclusion that despite the triggering trends and constraining factors of consumer purchasing behaviour, digital advertising remains viable as long as digitalization is metamorphic.